Diet and physical activity during the coronavirus disease 2019 (COVID-19) lockdown (March–May 2020): results from the French NutriNet-Santé cohort study. Issue 4 (1st March 2021) - Deschasaux-Tanguy, Mélanie; Druesne-Pecollo, Nathalie; Esseddik, Younes; de Edelenyi, Fabien Szabo; Allès, Benjamin; Andreeva, Valentina A; Baudry, Julia; Charreire, Hélène; Deschamps, Valérie; Egnell, Manon; Fezeu, Leopold K; Galan, Pilar; et al.
ABSTRACT: Background: Since December 2019, coronavirus disease 2019 (COVID-19) has been spreading steadily, resulting in overwhelmed health-care systems and numerous deaths worldwide. To counter these outcomes, many countries, including France, put in place strict lockdown measures, requiring the temporary closure of all but essential places and causing an unprecedented disruption of daily life. Objectives: Our objective was to explore potential changes in dietary intake, physical activity, body weight, and food supply during the COVID-19 lockdown and how these differed according to individual characteristics. Methods: The analyses included 37, 252 adults from the French web-based NutriNet-Santé cohort who completed lockdown-specific questionnaires in April–May 2020. Nutrition-related changes and their sociodemographic, lifestyle, and health-status correlates were investigated using multivariable logistic regression models. Clusters of participants were defined using an ascending hierarchical classification of change profiles derived from multiple correspondence analyses. Results: During the lockdown, trends of unfavorable changes were observed: decreased physical activity (reported by 53% of the participants), increased sedentary time (reported by 63%), increased snacking, decreased consumption of fresh food (especially fruit and fish), and increased consumption of sweets, cookies, and cakes. Yet, the opposite trends were also observed: increased home cooking (reported by 40%) and increased physical activity (reported by 19%). Additionally, 35% of the participants gained weight (mean weight gain in these individuals, 1.8 kg ± SD 1.3 kg) and 23% lost weight (2 kg ± SD 1.4 kg weight loss). All of these trends displayed associations with various individual characteristics. Conclusions: These results suggest that nutrition-related changes occurred during the lockdown in both unfavorable and favorable directions. The observed unfavorable changes should be considered in the event of a future lockdown, and should also be monitored to prevent an increase in the nutrition-related burden of disease, should these diet/physical activity changes be maintained in the long run. Understanding the favorable changes may help extend them on a broader scale. This trial was registered at clinicaltrials.gov as NCT03335644.